2013
DOI: 10.5194/bgd-10-14333-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of hypoxia and anoxia on invertebrate behaviour: ecological perspectives from species to community level

Abstract: Coastal hypoxia and anoxia have become a global key stressor to marine ecosystems, with almost 500 dead zones recorded wordwide. By triggering cascading effects from the individual organism to the community and ecosystem-level, oxygen depletions threat marine biodiversity and can alter ecosystem structure and function. By integrating both physiological function and ecological processes, animal behaviour is ideal for assessing the stress state of benthic macrofauna to low dissolved oxygen. The initial re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 112 publications
0
16
0
Order By: Relevance
“…In our study, genera Natica and Acteocina were collected in high oxygen concentrations in the north and central sections of the bay (stations 1, 3, 9, 4, 13, 14, 19, and 21). Although mollusks have been extensively employed in bioaccumulation studies for metal pollution [7,8,31], other studies have evaluated their utility as indicator of oxygen depletion in coastal environments [53,[55][56][57]. We acknowledge that only four genera of the thirteen dominant mollusks collected at TSB were related significantly to DO concentrations by a negative binomial GLM, which means that Truncatella, Donax, Bulla, and Acteocina follow a natural gradient of DO in Todos Santos Bay, Baja California.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, genera Natica and Acteocina were collected in high oxygen concentrations in the north and central sections of the bay (stations 1, 3, 9, 4, 13, 14, 19, and 21). Although mollusks have been extensively employed in bioaccumulation studies for metal pollution [7,8,31], other studies have evaluated their utility as indicator of oxygen depletion in coastal environments [53,[55][56][57]. We acknowledge that only four genera of the thirteen dominant mollusks collected at TSB were related significantly to DO concentrations by a negative binomial GLM, which means that Truncatella, Donax, Bulla, and Acteocina follow a natural gradient of DO in Todos Santos Bay, Baja California.…”
Section: Discussionmentioning
confidence: 99%
“…In the Adriatic Sea, Corbula gibba is a clear example of an opportunistic species [53] because it is frequently found in hypoxic conditions (<2 mL L −1 ) and after postanoxic periods [54,55]. It has been demonstrated that C. gibba can survive for 78 h in anoxic conditions [56]. In the present study, Dentalium, Chione, Laevicardium, and Nuculana were found in low DO concentrations (<2 mL L −1 ); furthermore, these genera of bivalves are relatively tolerant to low oxygen levels in Todos Santos Bay.…”
Section: Discussionmentioning
confidence: 99%
“…temperature, hypoxia, food shortage, suspended matter) compounding the impact of any single environmental stress (such as CO 2 exposure from CCS leakage) and severely inhibiting the scope for physiological and behavioural adjustments to overcome that stress (Riedel et al, 2014;Queirós et al, 2015). It is unlikely therefore that hypercapnia will act as a single stressor, and caution is needed when assessing tolerances of species to environmental perturbations from studies that have only factored in one variable.…”
Section: Summary Of Advances In Impact Understandingmentioning
confidence: 99%
“…The chamber, originally designed to document macrofauna behaviour during low-DO conditions (see also Riedel et al, 2013), is equipped with a digital camera (Canon EOS 30D; images taken in 6 min intervals), underwater flashes and a sensor array (DO, hydrogen sulphide H 2 S). The sensors were positioned 2 cm above the sediment and values were recorded in 1-min intervals.…”
Section: In Situ Experimental Set-up and Samplingmentioning
confidence: 99%